Print Media, Governance and Anti-Corruption Programmes in Nigeria - Kupoluyi, Adewale K.; Nwaodike, Chibuzor A.; Ntiwunka, Gift U. (NIU Journal of Humanities, 2020)
Corruption is the bane of good governance and as such prevents a country from providing basic needs for its citizens. In Nigeria, despite the series of anti-corruption programmes and the activities of the print media, cases of corruption still persist. The main objective of the study was to examine the role of the print media in the prosecution of anti-corruption programmes in Nigeria. The study adopted descriptive survey which combined both qualitative and quantitative methods. 10 print media organizations in Nigeria were purposively selected as population. These include The Punch, The Nation, The Guardian, The Sun, Nigerian Tribune, This Day, Vanguard, Daily Trust, The News, and Tell. The sample size was limited to Federal Capital Territory, Abuja and Lagos State through multi stage sampling. The reason for choice of the sample size is that Abuja and Lagos are the hub of media establishments and highly cosmopolitan locations in Nigeria. Survey and interview methods were used to administer and obtain data from eight hundred and twenty (820) respondents and sixteen (16) interviewees respectively. Quantitative data was analyzed using descriptive statistics in tables, percentages, mean and standard deviation, while the qualitative data from the media organizations were content analyzed. Findings revealed that the print media ensured that corruption cases were properly reported and prosecuted (Mean = 3.7425, St.D = 1.23216); encouraged collaboration among the different anti-graft agencies (Mean = 3.6459, St.D = 1.07545); lacked the political-will to fight graft; embarked less on investigative journalism; and unduly influenced by proprietors.  The study concluded that the print media was instrumental to anti-corruption programmes during the period of the study (1999-2019). The paper recommended that the print media should engage more in investigative journalism, develop the political-will to fight corruption, and proprietors should desist from unduly influencing journalists while performing official duties to enable the print media contribute better towards the implementation of anti-corruption programmes in Nigeria. Keywords: Print Media , Anti-Corruption, Democratization, Governance, Agency.